A comparative study of hypofractionated and conventional radiotherapy in postmastectomy breast cancer patients - Kartick Rastogi; Sandeep Jain; Aseem Rai Bhatnagar; Sandeep Bhaskar; Shivani Gupta; Neeraj Sharma (Asia-Pacific Journal of Oncology Nursing, 2018)
Objective: The aim of this study was to compare toxicity and locoregional control of short duration hypofractionated (HF) radiotherapy (RT) with conventional RT in breast cancer patients. Methods: A total of 100 postmastectomy breast cancer patients were randomized for adjuvant RT in control group (comprising fifty patients who received the standard conventional dose of 50 Gy in 25 fractions with 2 Gy per fraction) and study group (comprising fifty patients who received HF RT with dose of 42.72 Gy in 16 fractions with 2.67 Gy per fraction). All patients were treated on linear accelerator with 3-dimensional conformal RT technique. Outcome was analyzed in terms of toxicity, tolerability, and locoregional control. Results: In the present study, at a median follow-up of 20 months, almost similar results were seen in both the groups in terms of toxicity, tolerability, and locoregional control. Adjuvant postmastectomy HF RT was found to be well tolerated with mild-to-moderate side effects that neither reached statistical significance nor warranted any treatment interruption/hospitalization. Conclusions: HF postmastectomy RT is comparable to conventional RT without evidence of higher adverse effects or inferior locoregional tumor control and has an added advantage of increased compliance because of short duration; hence, it can help in accommodating more breast cancer patients in a calendar year, ultimately resulting in decreased waiting list, increased turnover, and reduced cost of treatment.